All Days 2013
DOI: 10.2118/167129-ms
|View full text |Cite
|
Sign up to set email alerts
|

Tip-Effect Microseismicity - Numerically Evaluating the Geomechanical Causes for Focal Mechanisms and Microseismicity Magnitude at the Tip of a Propagating Hydraulic Fracture

Abstract: There have been extensive industry efforts to understand the geophysical implicationsand limitationsof microseismic analyses; however, a critical issue that is often overlooked is the geomechanics of the rock failure that is represented by microseismicity. Recall that microseismicity is the acoustic representation of rock failure, whether tensile failure or shear failure, which is driven by the coupled hydro-thermo-mechanical effects of injecting cool fluids at high rates into naturally fractured formations. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The excellent agreement between the true fracture length and the observed microseismic length implies that at least some of the microseisms are generated in the vicinity of the tip of the fracture, and the detection of those microseisms provides accurate length assessment. Such behavior is fully expected from geomechanics considerations (Warpinski et al 2004;Agharazi et al 2013). Cipolla (2015) presents a single result for a fracture hit in a horizontal pad development in the Bakken in North Dakota.…”
Section: Fracture Lengthmentioning
confidence: 63%
“…The excellent agreement between the true fracture length and the observed microseismic length implies that at least some of the microseisms are generated in the vicinity of the tip of the fracture, and the detection of those microseisms provides accurate length assessment. Such behavior is fully expected from geomechanics considerations (Warpinski et al 2004;Agharazi et al 2013). Cipolla (2015) presents a single result for a fracture hit in a horizontal pad development in the Bakken in North Dakota.…”
Section: Fracture Lengthmentioning
confidence: 63%
“…The shear stimulation due to changes in stresses is mainly driven by the propagation of a new hydraulic fracture. Agharazi et al (2013) and Nagel et al (2014) showed that a high shear zone develops at the tip of a propagating hydraulic fracture that moves with the propagating fracture tip. Natural fractures that fall inside this shear zone experience an increase in shear stresses and may slip, depending upon their orientation and shear strength characteristics.…”
Section: Dominant Stimulation Mechanismmentioning
confidence: 99%
“…Behind the shear zone, a compressive zone forms on either side of the fracture with lower shear stresses (Agharazi et al 2013 andNagel et al 2014). Within this region, the buildup of pore pressure due to fluid leakoff into formation is the only mechanism that can cause shear failure (wet events) on natural fractures.…”
Section: Dominant Stimulation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The worldwide boom in coalbed methane, shale gas and other unconventional developments is now well-known, and the boom has had a significant impact on the balance of hydrocarbon production [1] . There's general agreement that coal is composed of micro and nanopores, with the majority being nanopores.…”
Section: Introductionmentioning
confidence: 99%